2004
DOI: 10.1073/pnas.0400938101
|View full text |Cite
|
Sign up to set email alerts
|

Body plan evolution of ascomycetes, as inferred from an RNA polymerase II phylogeny

Abstract: The mode of evolution of the biologically diverse forms of ascomycetes is not well understood, largely because the descent relationships remain unresolved. By using sequences of the nuclear gene RPB2, we have inferred with considerable resolution the phylogenetic relationships between major groups within the phylum Ascomycota. These relationships allow us to deduce a historical pattern of body plan evolution. Within Taphrinomycotina, the most basal group, two simple body plans exist: uncovered asci with unicel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
107
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(120 citation statements)
references
References 33 publications
12
107
0
1
Order By: Relevance
“…The tree is robust with bootstrap values of 100% at most nodes and is in accord with organismal phylogeny. The grouping of C. glabrata and S. cerevisiae in a single clade is in agreement with recent phylogenetic analyses [28,29]. The lower bootstrap support for the grouping of S. pombe and N. crassa reflects their placement in different clades in the phylum Ascomycota [29].…”
Section: Comparison and Phylogenetic Analysis Of Tps Protein Sequencessupporting
confidence: 90%
“…The tree is robust with bootstrap values of 100% at most nodes and is in accord with organismal phylogeny. The grouping of C. glabrata and S. cerevisiae in a single clade is in agreement with recent phylogenetic analyses [28,29]. The lower bootstrap support for the grouping of S. pombe and N. crassa reflects their placement in different clades in the phylum Ascomycota [29].…”
Section: Comparison and Phylogenetic Analysis Of Tps Protein Sequencessupporting
confidence: 90%
“…The results showed that the Taphrinomycotina genetic characteristics show greater similarity to those of filamentous ascomycetes than to those of ascomycetous yeasts. The results also support the notion that ancestral ascomycetes were filamentous and that hyphal growth was lost independently (Liu and Hall, 2004). Taphrinomycotina is the earliest ascomycetous lineage that diverged before the separation of the subphyla Pezizomycotina and Saccharomycotina (Nishida and Sugiyama, 1993;An et al, 2002;Liu et al, 2009;Schoch et al, 2009).…”
Section: Discussionsupporting
confidence: 70%
“…Initial analyses using DNA sequence data from the small subunit ribosomal RNA gene did not support the monophyly of the Loculoascomycetes (Spatafora et al 1995, Berbee 1996. A more recent phylogeny produced from protein gene coding data (Liu and Hall 2004) was inferred as supporting the taxonomic concepts for a monophyletic lineage for ascostromatic taxa, but the ontogenetic designations were considered oversimplified by some (Lumbsch et al 2005). Other studies combining data from protein-coding genes and the ribosomal operon have shown the paraphyly of ascostromatic, bitunicate lineages , Reeb et al 2004.…”
Section: Introductionmentioning
confidence: 99%